AN ANALYSIS ON THE PHONOLOGICAL ERRORS MADE BY ENGLISH DEPARTMENT STUDENTS OF LAMBUNG MANGKURAT UNIVERSITY - Novianto, Catur Bayu (Universitas Lambung Mangkurat, 2019)
Pronunciation is very important skill in learning English. To acquire good pronunciation skill, the English learners are expected to pronoun English sound and so its stress word based on the phonological features. However, phonology the study of speech sound, has many aspects or features such as segmental or suprasegmental that sometimes bring difficulties to students. Then, the problems may appear if students cannot produce the appropriate speech sound based on its features because of the complexity of its phonological system. Since the segmental feature is related with the speech sound emitted by the speech organs, this study is set to examine only the English voiced-voiceless consonant sound as the limitation of the study. Similarly, in the suprasegmental feature, the aspect of word and sentence stresses are also set to examine. It is essentially important that the English sounds should be pronounced based on the appropriate utterances and the stress pattern to deliver the right meaning of what speaker wants to say. Even it is not directly or clearly changed the meaning of the word, but if the speakers produce the different utterances from the features, the pronunciation will be not sounded English. Thus, this recent study aims to examine the pronunciation errors of English Department students in pronouncing English voiced-voiceless consonant sounds which do not exist in the students’ first language and giving stress to English words and sentences.